A comprehensive genome survey study unveils the genomic characteristics and phylogenetic evolution of fishes in the Uranoscopidae family - Liu, Qi; Zhao, Xiang; Qu, Yinquan; Wang, Yiting; Guo, Xingle; Li, Wenyu; Gao, Tianxiang; Qiao, Ying (Frontiers in Marine Science, 2024)
The construction of high-quality genomes is fundamental for molecular studies of species. Currently, there are no published genome sequences within the Uranoscopidae family, and research on the genomic characteristics of this family is lacking. In this study, genomic analyses of seven species from the Uranoscopidae family which captured from the southeastern coast of China were conducted using next-generation sequencing technology. The results revealed that the genomic characteristics of the seven species are relatively similar. The genome sizes of the seven Uranoscopidae species ranged from 536.00 Mb to 652.49 Mb, with repeat sequence proportions between 20.09% and 36.64%, and heterozygosity levels ranging from 0.41% to 0.88%. The assembled draft genomes exhibited GC contents of these species ranging from approximately 42.14% to 43.53%. Furthermore, the mitochondrial sequences for the seven species were assembled, with sizes ranging from 14,966 to 18,446 bp. The evolutionary relationships between different species were depicted through the mapping of conserved genes, whole-genome variances and mitochondrial genome sequences. Besides, the historical effective population sizes of all species experienced rapid expansion after the Last Interglacial Period, with three species undergoing bottleneck effects. In conclusion, this study provides a reference for the subsequent construction of high-quality genomes for species within the Uranoscopidae family and offers a rich data resource for further evolutionary research.